Critical Thinking in Curriculum Practice: The Case of Higher Institutions of Learning in Uganda - Katende, Esther (Journal of Education and Practice, 2023)
Purpose: The purpose of this study is to explore the nature of critical thinking in curriculum practice in higher institutions of learning in Uganda. The study is based on Makerere University Business School, as a case study of institutions of higher learning in Uganda. Methodology: The methodology used is textual analysis of curriculum documents, non participatory overt classroom observation and focused interviews of the lecturers who teach the observed classes, to determine whether in practice, critical thinking is actually taught to learners. Findings: It is the finding of this research that the curriculum practice in Uganda generally uses methods that do not strongly support the development of critical thinking skills in learners. The over-dependence on the lecture method causes the learners to fall short of the key Taxonomic words that build critical thinking skills in learners. Unique contributor to theory, policy and practice: This study is a unique contribution to theory and practice as it shows the implementation of critical thinking in the classroom in Uganda in relation to Bloom's Taxonomy.